Book review:Asaf Friedman, Art and Architecture of the Synagogue in Byzantine Palaestina, Cambridge: Cambridge Scholars Publishing, 2019 - WEISS, Zeev (Byzantina Symmeikta, 2021)
Book Review:Asaf Friedman, Art and Architecture of the Synagogue in Byzantine Palaestina, Cambridge: Cambridge Scholars Publishing, 2019